2017
DOI: 10.1371/journal.pone.0184781
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ treatment in vitro elicits some of the changes in cathepsin S and antigen presentation characteristic of lacrimal glands and corneas from the NOD mouse model of Sjögren’s Syndrome

Abstract: Inflammation and impaired secretion by lacrimal and salivary glands are hallmarks of the autoimmune disease, Sjögren’s Syndrome. These changes in the lacrimal gland promote dryness and inflammation of the ocular surface, causing pain, irritation and corneal damage. The changes that initiate and sustain autoimmune inflammation in the lacrimal gland are not well-established. Here we demonstrate that interferon-γ (IFN-γ) is significantly elevated in lacrimal gland and tears of the male NOD mouse, a model of autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 46 publications
5
35
0
Order By: Relevance
“…Gene expression of Ctss, together with the pro-inflammatory cytokines, Ifng and Tnf, were significantly elevated in NOD mouse LG ( Fig. 2A) consistent with previous reports 13 . No changes in Cx3cl1 gene expression were observed ( Fig.…”
Section: Cx3cl1 and Ctss Are Increased In Nod Mousesupporting
confidence: 91%
See 2 more Smart Citations
“…Gene expression of Ctss, together with the pro-inflammatory cytokines, Ifng and Tnf, were significantly elevated in NOD mouse LG ( Fig. 2A) consistent with previous reports 13 . No changes in Cx3cl1 gene expression were observed ( Fig.…”
Section: Cx3cl1 and Ctss Are Increased In Nod Mousesupporting
confidence: 91%
“…previously demonstrated increased IFN-γ in tears of male NOD mice 13 . From mouse corneal cross sections, we found that CX3CL1 was mainly distributed in the corneal epithelium.…”
Section: Ifn-γ Treatment Increases Cx3cl1 In Hce-t Cells and Culture mentioning
confidence: 78%
See 1 more Smart Citation
“…Cathepsins degrade ECM proteins, including collagens, laminins, and proteoglycans. [76][77][78][79] Additionally, NID1 binding to the BM is impaired after cleavage by CTSS, 80 which was transcriptionally enhanced in kidney AMR 27 and in response to IFNɣ [81][82][83] . In PTECs, CTSS and LGMN were upregulated by TNFα and IFNɣ.…”
Section: Discussionmentioning
confidence: 99%
“…Activation. CatS is essential in MHC II antigen processing and presentation [92,93]. Indeed, CatS null mice show a considerable variation in generation of MHC II-bound Ii fragments, and presentation due to the fact that the Ii degradation in professional APCs is substantially diminished, where CatS is abundantly expressed [94,95].…”
Section: Cats In Mhc II Antigen Presenting and Cd4 + T-cellmentioning
confidence: 99%